The bond strength of root canal filling after calcium hydroxide removal with a simple apical negative pressure kit in oval-shaped root canal - Warat Leelapornpisid; Thanapat Sastraruji; Phumisak Louwakul; Anat Dewi (Wolters Kluwer Medknow Publications, 2023)
Background: The aim of this study was to evaluate the effect of a simple irrigating device, which produced from the apical negative pressure concept, as a final irrigating method after calcium hydroxide (CH) medication on the bond strength of epoxy resin-based sealer in the oval-shaped root canal. Methods: Forty-eight single-rooted premolars with oval-shaped canals were included in the study. The crown was decoronized and canal instrumented with Mtwo (VDW GmbH, Munich, Germany) up to size 40/04. The specimens were assigned to four groups according to the irrigation protocol after 1 week of CH medication: control group (no medication) and three experimental groups conventional needle irrigation (CNI), passive ultrasonic irrigation (PUI), and simple apical negative pressure kit (sANP). The teeth were obturated with a warm vertical technique using epoxy resin-based sealers. After 1 week, the roots were transversally sectioned at coronal, middle, and apical thirds. A push-out test was performed by a universal testing machine, and statistical analysis was performed using One-Way ANOVA with Duncan's post hoc test. Results: The bond strength in the control group was significantly higher than the CNI group in all root canal thirds (P < 0.05). At coronal third, sANP showed lower bond strength than PUI group (P < 0.05). However, the bond strength of sANP group was comparable to the control group (P > 0.05) which was significantly higher than the PUI group at apical third (P < 0.05). Conclusion: A sANP enhanced the bond strength of epoxy resin-based sealer in the apical third of CH-medicated root canal in the oval-shaped canal.